2020
DOI: 10.1039/c9ra08692g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis of cobalt telluride nanorods for a high performance hybrid asymmetric supercapacitor

Abstract: A one-step hydrothermal derived cobalt telluride nanorods and activated carbon-based hybrid asymmetric supercapacitor delivered a high energy (40.7 W h kg−1) and power density (22.5 kW kg−1) with an electrochemical stability of 85% for 10000 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…The Ragone plot clearly shows that the symmetric supercapattery device can deliver a high energy density without sacrificing much on power density. The high energy and power densities of the fabricated supercapattery device are significantly greater than the reported values (Figure ) for symmetric and asymmetric supercapacitors in aqueous electrolyte. …”
Section: Results and Discussionmentioning
confidence: 65%
“…The Ragone plot clearly shows that the symmetric supercapattery device can deliver a high energy density without sacrificing much on power density. The high energy and power densities of the fabricated supercapattery device are significantly greater than the reported values (Figure ) for symmetric and asymmetric supercapacitors in aqueous electrolyte. …”
Section: Results and Discussionmentioning
confidence: 65%
“…In addition, the final nanocomposite shows unique meso- and micro-porous structures with a high specific surface area, which could improve the easy electron transfer during electrochemical performance when used as an electrode material. This might be an extra benefit of the electrode material during electrochemical applications [ 42 ]. Table 1 lists the BET specific surface area, average pore size, and pore volumes of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Manikandan et al reported the fabrication of cobalt telluride nanorods (CoTe) and Te nanorods. CoTe exhibited C sp ∼ 170 C/g @ 0.5 A/g which was found that higher than Te nanorod 80 F/g ( Manikandan et al, 2020 ). Moreover, they reported nickel telluride to attain C sp > 610 F/g @ 1 A/g ( Manikandan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 89%